Strategi Komunikasi Pemasaran Musik Independen “Album Generation Y” Kunto Aji - Dyah Lestari, Erika; Hasfi, Nurul (Interaksi Online, 2019)
This qualitative research used the basic concept of SOSTAC Analysis and Persuasive Communication Technique along with previous journals to explain the research findings. Qualitative descriptive approach and domain-qualitative analysis had also been used to further analysed the findings in this research. The data of the research was collected through series of interviews and observations of Kunto Aji himself, his label management and his fans. The result of this study shows that there was a digital platform utilization and an intimate fans-artist relationship development analysed with SOSTAC Analysis and Persuasive Communication Technique respectively. Kunto Aji owns an Indie recording label that he managed with his management team. The study found that establishing an intimate relationship between Kunto Aji and his fans had have effects on many aspects, such as improved level of loyalty among his fans. The fans showed their ‘loyalty’ by supporting Kunto Aji’s work, from buying his latest album called Generation Y and his art works, to covering his songs then posting it on social media. The constant support that the fans gave also had contributed in Kunto Aji winning many awards both in Indonesia and International. There are some suggestions researcher would like to give to Kunto Aji and his management, such as to improve consistency at conducting events like “Temu Akhir Bulanan” to maintain fans-artist intimacy and to incorporate more creative and unique innovation in his upcoming work.